Discursive power and environmental justice in the new South Africa: the Steel Valley struggle against pollution (1996-2006) - Munnik, Albert Victor (My University, 2013)
The study explores the thesis that discursive power played a major role in the pollution and subsequent destruction of Steel Valley to explain why, despite strenuous efforts by local citizens, the right to live in a healthy environment, guaranteed in the new South African constitution, was not upheld. It analyses the struggle in Steel Valley around the definition of pollution, and decision making about its consequences, in terms of discursive resources and their deployment in discursive arenas, focusing on discursive strategies of the polluted, the polluter and the regulator. This exploration is set within the politics of hegemony in a new South Africa after 1994, as well as the 120 year old Minerals Energy Complex at the centre of the South African political economy. It explains the legitimation of pollution in Steel Valley within the global discourses of environmental management, ecological modernisation and sustainable development prominent since the 1990s. Discursive power played a major role in the Steel Valley case. Discursive power led to the material outcomes in Steel Valley: the removal of the community, the physical destruction of their buildings and the transformation of the area into a “conservation” buffer zone, along with decisions not to pay residents compensation and not to establish a medical trust. Discursive power was used by the polluter to escape liability, by maintaining scientific and legal uncertainty about the nature, extent and consequences of the pollution. Discursive power enabled the polluter to frame the problem as one of ecological modernisation from which social justice concerns, like compensation, could be excluded. ISCOR’s discursive power also overwhelmed the regulator, as the regulator remained too cautious to use to the full the instruments available to it in law, and allowed numerous exemptions. The state and the polluter both pushed issues of Environmental Justice – compensation and rehabilitation – outside the dominant frame of decision making. The study shows how a superiority of discursive resources on the side of the polluter, derived from a financial and political superiority, translated into decisive defeats for the 4 Steel Valley community. This superiority derived from a constellation of discursive conditions in scientific, legal and administrative arenas. To describe these conditions, the study constructs a description of a pollution dispositive at work in Steel Valley, which legitimises past and future pollution. It explains the choices of the new government as pollution regulator, by understanding the tax-dependent state as responsive to both legitimacy and accumulation pressures within a hegemonic growth discourse. A grounded theory approach is followed to study discursive power, synthesizing elements of the social and narrative construction of reality, Critical Discourse Analysis, dispositive analysis and the Environmental Justice approach. It develops a variant of Critical Discourse Analysis that can work across a big case study, by treating discursive power plays as part of a pollution dispositive, which is an assembly of heterogeneous elements (practices and knowledges) that can be understood together as a strategic response to an emerging situation. The pollution dispositive was composed of pre-existing resources available in its environment: local discourses producing disposable others, through racism or a view of dispensable fenceline communities; the legitimations and limitations of the politics of hegemony, and the discourses of growth, limited corporate liability, as well as of environmental management, sustainable development and ecological modernisation. The study explores the implications of this analysis for Environmental Justice tactics in the areas of environmental management, citizen science, the politics of ecological modernisation, and the politics of hegemony in the new South Africa. It shows that the conditions of fenceline communities and the nature of discursive struggles around them create a tactical terrain which can be used to advance the cause of Environmental Justice. In the tradition of critical theory, it contributes to the understanding of anti-pollution struggles within the Environmental Justice movement, engaging with a triad of concepts that explain the imposition of environmental injustice: externalisation of the costs of pollution, exclusion from decision making and enclosure of resources. This approach can be applied to the environmental struggles of other communities on the fencelines of the Minerals Energy Complex in South Africa.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, December 2012
Keywords: Pollution.; Pollution - South Africa - Steel Valley.; Pollution - Social aspects.